Cell-tracking with lightning data from LINET - H. D. Betz; K. Schmidt; W. P. Oettinger; B. Montag (Advances in Geosciences, 2008)
A new lightning detection network (LINET) has been developed at the University of Munich, which locates and reports both cloud discharges and cloud-to-ground strokes with high accuracy. The network started operation in May 2006; since then lightning data for Europe are being delivered to many scientific groups, and to the German Weather Service (DWD) on an operational basis (powered by nowcast GmbH, Germany). Using about 90 lightning sensors in 17 countries, an area from longitude 10° W–25° E to latitude 35° N–65° N is covered. Further expansion is in the planning stage with the aim to attain higher efficiency for Mediterranean storms. The total lightning capability, not readily available otherwise in large areas, is particularly helpful because it can provide useful information about the development of severe weather and strong storm cells. A cell-tracking module has been developed that allows the investigation of lightning parameters for specific convective cells. Present efforts are devoted to the question for what kind of storms and to what extent lightning-based cell tracking allows improved nowcasting. Numerous case studies have been carried out and typical examples will be presented.